Comparison of the abrasive properties of two different systems for interproximal enamel reduction: oscillating versus manual strips - Francesca Gazzani; Roberta Lione; Chiara Pavoni; Gianluca Mampieri; Paola Cozza (BMC, 2019)
Abstract Background The aim of the present investigation was to evaluate enamel reduction efficiency, abrasive property decay, and enamel effects between oscillating mechanical and manual systems for interproximal enamel reduction (IPR). Methods Three oscillating strips and three manual strips were tested on twelve freshly extracted premolars blocked in an acrylic cylinder pot by means of a material testing machine. Each strip underwent one test of 8 cycles (30 s each). Both abrasive tracks and teeth surfaces were qualitative evaluated before and after IPR by means of SEM analysis. Efficiency and abrasive property decay of both IPR systems were investigated by the amount of enamel reduction within the eight-cycle testing. Independent t-test was used to evaluate differences in variables between the two systems. Results Mechanical IPR system showed higher efficiency in terms of enamel reduction (p < 0.005) when compared with manual IPR system (0.16 mm and 0.09 mm, respectively). Quantity of removed enamel decreased throughout the 8 cycles for both systems. Less presence of enamel debris and detachment of abrasive grains were observed on mechanical strips rather than manual strips. SEM analysis revealed more regular surface of teeth undergone mechanical IPR procedures. Conclusion Oscillating diamond strips showed more controlled efficiency when compared with the manual IPR system leading to a more regular enamel surface.